Hydrogen peroxide on fresh cut snap bean pathogens control and enzymatic browning - de Arruda Palharini, Maria Cecília; de Júlio Pereira Santos, Claudia Aline; de Souza Fileti, Mirian; Ravási Stéfano Simionato, Eliane Maria; Cerqueira Sasaki, Fabiana Fumi (Comunicata Scientiae, 2017)
The objective of this study was to evaluate the efficacy of sanitization with hydrogen peroxide in reducing the enzymatic browning and pathogens of fresh cut snap bean. Fresh cut snap beans were inoculated by immersion in an Escherichia coli and Salmonella enteritidis contaminant solution Then, the vegetable was sanitized with hydrogen peroxide (0; 5; 10 and 20 mL L-1) for 10 minutes. The pathogens were monitored immediately after sanitization and after 4 days of storage at 10ºC. In other similar experiment, but without inoculation of pathogens, the snap bean were evaluated periodically. The surface color, pH, activity of phenylalanine ammonia-lyase, peroxidase and polyphenoloxidase enzymes, chlorophyll and carotenoids contents were evaluated. The sanitization with hydrogen peroxide reduced the count of E. coli and S. enteritidis, being similar for different hydrogen peroxide concentrations. The browning of the section surface of snap bean was controlled by hydrogen peroxide in the concentration of 20 mL L-1. The activity of the enzymes as well as the pigments content (chlorophyll and carotenoids) were not affected by treatments, except the polyphenoloxidase enzyme. The pH increased during storage and was greatest in snap bean sanitized with 20 mL L-1. The sanitization with hydrogen peroxide is effective in reducing population of E.coli and S. enteritidis and minimizing browning in fresh cut snap bean, but caused spots on the vegetable skin, precluding its use.